Transformasi Ekonomi Digital dan Kinerja UMKM: Analisis Pengaruh Digitalisasi Akuntansi Terpadu: Digital Economic Transformation and MSME Performance: An Analysis of the Impact of Integrated Accounting Digitalization - Fransisca Dyah Anggraini; Khairunnisa Khairunnisa (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: This study aims to analyze the effect of implementing an integrated digital accounting system on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Palembang City. Design/Methodology/Approach: This research employs a quantitative approach, with data collected through structured questionnaires distributed to 100 MSME actors. The analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4.0 software. Findings: The results reveal that the implementation of a digital accounting system has a positive and significant effect on performance, where 87% of the variation in MSME performance can be explained by the adoption of the digital accounting system, while the remaining variation is influenced by factors outside the model. Implications: The adoption of digital accounting can serve as a crucial strategy to enhance MSME competitiveness. From a policy perspective, government support is needed in the form of digital infrastructure provision, literacy programs, and technology-based accounting training.